The complete dog breed book - Bryan, Kim; Morgan, Tracy (2020)
From the tiny Chihuahua to the towering Great Dane, discover all there is to know about hundreds of dog breeds from across the world in this stunning DK encyclopedia that covers all things canine. Combining breeds, behaviour, care, and training advice, this book contains everything you need to know to help you choose and care for a dog. Find the perfect pet using Q&A selector charts that help you find the best breed to suit your lifestyle. Fully updated to reflect the latest dog breeds, The Complete Dog Breed Book contains a catalogue of more than 420 dogs. Each features stunning photographs of the dog from various angles, while popular breeds - including the Boxer, Labrador Retriever, and English Springer Spaniel - are given a special in-depth treatment. Clear and concise text explains the main features of the dog, as well as providing a historical overview of the breed. Annotation highlights physical characteristics of each breed, while panels provide an at-a-glance guide to key features, such as the dog's temperament, size, and colour. A practical section on care covers the fundamental aspects of looking after a dog, from handling and grooming to exercise and health. Step-by-step photographic sequences, combined with expert-written advice, explain the essentials of basic obedience. The Complete Dog Breed Book is a one-stop manual to helping you become the owner of a happy, healthy, well-behaved dog.--
"Previously published as Top dog"--Cover.
Includes index.
Keywords: Dogs -- Encyclopedias; Dog breeds -- Encyclopedias; Dog breeds; Dogs; Dogs -- Encyclopedias